2021
DOI: 10.1371/journal.pone.0261199
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic, lifestyle, behavioral, and parental factors associated with sugar-sweetened beverage consumption in children in China

Abstract: Objective Evidence shows sugar-sweetened beverage (SSB) consumption is a risk factor for obesity and non-communicable diseases (NCDs) in children. Investigating the influential profiles, which have been examined insufficiently, will help to inform the reduction of SSB consumption. The present research examines the current trend in SSB consumption and associated factors among children in China, in order to inform policy development. Methods Secondary data was extracted from China’s Health and Nutrition Survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 48 publications
3
15
1
1
Order By: Relevance
“…The present study showed that caregivers' rates of SSB consumption [24,40] and taking children to fast-food restaurants [41][42][43] frequently were positively associated with SSB consumption among their children, consistent with previous studies at home and abroad. Our study also identified that as low as one-third of caregivers read the NFPs frequently, which was negatively associated with SSB consumption among their children.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The present study showed that caregivers' rates of SSB consumption [24,40] and taking children to fast-food restaurants [41][42][43] frequently were positively associated with SSB consumption among their children, consistent with previous studies at home and abroad. Our study also identified that as low as one-third of caregivers read the NFPs frequently, which was negatively associated with SSB consumption among their children.…”
Section: Discussionsupporting
confidence: 92%
“…Data on the child’s birth date, gender, family income, and whether the child was the only child in the family were also collected using questionaries. Family income based on the “annual household income per capita” item of this study and ranging from “50 thousand RMB/year or below” to “more than 150 thousand RMB/year” was used as a proxy for socio-economic status [ 17 , 22 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SSB consumptions per person are still increasing ( Popkin and Hawkes, 2016 ). In China, the percentage of SSB consumption in children increased from 72.6 to 90.3% in 2004–2011 ( Guo et al, 2021 ). During the COVID-19 pandemic and lockdown, changes in dietary behavior factors include increased total food consumption, decreased adherence to healthy diets, and increased snack and SSB intake ( Chew and Lopez, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Family factors have been proved to be one of the main influencing factors affecting children's SSB consumption, and associations between family members' SSB consumption and children's diet with high SSB intake have been found in cross-sectional studies [1,[5][6][7][8][9][10][11][12][13]. While the correlation is strong, it is not possible to unequivocally determine the direction of causality.…”
Section: Introductionmentioning
confidence: 99%